SIMPLE WAYS TO IMPROVE ENGLISH SPEAKING IN TEACHING AND LEARNING - MAM Socheath (University of Muhammadiyah Purwokerto, 2010)
Most learners of English as Foreign Language find it difficult to dealwith English Productive Skills–Speaking and Writing in effectiveways. Because of the poor level ability in speaking and writing,students are failed to make an effective communication in Englishlanguage. Some learners feel shy, even shameful, to speak in Englishas they are afraid of making mistakes. Instead, they usually use theirown language while working in pair or group. It is noticed thatmany learners lack the confidence to speak in English, so we need tofind ways of developing their communicative competence andmotivate them through fun, stimulating, non-threatening activities.English Speaking is not too easy, not really difficult though. Thispaper will present some effective ways to help learners either buildthe better ability in English speaking or lead themselves towardbetter communication skills in English language. Additionally, thepaper will demonstrate some funny and interesting speakingactivities related to daily life communication as well as classroomactivities. That will be helpful for both learners and teachers ofEnglish as Foreign Language.